Determinanty defektywnego międzyosobowego komunikowania się w relacjach polsko-rosyjskich - Woźniewicz, Władysław (Studia Rossica Posnaniensia, 2018)
In the introductory part, the author defines the basic terms used in the article: culture, cultural norms, language-communication skills, knowledge and its deficits, intercultural communication in Polish-Russian relations and the concept of defective communication. The purpose of this article is to describe the various causes of defective communication in Polish-Russian relations. In the following sections of the article, the author describes and exemplifies symptoms of defective communication, the over-ethnic causes of communication failures, the ethnic Polish-Russian determinants of defective interpersonal communication related to knowledge deficits, Russian language skills and stricte cultural determinants of unfortunate communication in selected spheres of life.